2018
DOI: 10.1093/fampra/cmy072
|View full text |Cite
|
Sign up to set email alerts
|

Videoconferencing psychological therapy and anxiety: a systematic review

Abstract: Results provide promise for evidence-based interventions delivered via videoconferencing psychological therapy. More rigorous research is needed in various settings and populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
88
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(101 citation statements)
references
References 42 publications
4
88
0
9
Order By: Relevance
“…Our results showed how MHWs adopted remote work practices. Tele-psychiatry practices have been tested in different contexts and can be useful and effective for both psychiatric assessment and monitoring interventions [28,29], individual psychotherapy [30,31] and group interventions [32]. Online psychological support programs have been reported in several countries during the Covid-19 pandemic, including China [33], Germany [34], the United States [35], and France [36].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed how MHWs adopted remote work practices. Tele-psychiatry practices have been tested in different contexts and can be useful and effective for both psychiatric assessment and monitoring interventions [28,29], individual psychotherapy [30,31] and group interventions [32]. Online psychological support programs have been reported in several countries during the Covid-19 pandemic, including China [33], Germany [34], the United States [35], and France [36].…”
Section: Discussionmentioning
confidence: 99%
“…Conducting exposure to interoceptive cues in a context where the patient is far away from the therapist is an important asset for the generalization of the current study to the situation imposed by the COVID-19 and public health rules related to physical distancing and confinement. Actually, most past VCP studies did not conduct randomized control trials (Berryhill et al, 2019). The 12-month follow-up must be interpreted in the context of an intent-to-treat analysis where some patients could not be reached to collect information.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of CBT is well established in the treatment of anxiety disorders when delivered face-to-face, when compared to no treatment or to a placebo (Hofmann et al, 2012;Carpenter et al, 2018), and is recommended as the gold-standard form of psychotherapy for PDA in clinical guidelines (e.g., Katzman et al, 2014). Several outcome studies have been conducted on VCP, but systematic reviews on anxiety disorders have always concluded that more rigorous research is needed (Rees and Maclaine, 2015;Berryhill et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations